Ultraprecision Machining of Silicon Wafer by Micromilling Process. (2017) - Golshan, A.; Baharudin, B.T.H.T.; Aoyama, H.; Ariffin, M.K.A.M.; Ismail, M.I.S.; Ehsan, A.A.
Abstract: Silicon, being a material which allows light transmission beyond visible spectrum is a good candidate for the integration of microfluidic and optical devices. The lack of rapid prototyping method in particular mechanical-based micromachining process for silicon device processing is due to the brittleness property of silicon. Silicon fails or breaks without significant deformation when subjected to tension or stress. This study presents an experimental investigation on surface of micro-machined single-crystal silicon with (111) orientation. Full immersion slot milling was conducted using solid cubic boron nitride (CBN) micro-end mills. Influences of cutting parameters including spindle speed, feed rate and axial depth of cut on surface roughness were analyzed. Surface and subsurface characterization studies show that the primary material removal mode is ductile or partial ductile using lower feed rate.